Feminist Approaches to Childhood: From Children as a Silent Social Group to Giving Voice to Children - Golubović, Andrija (Zbornik Instituta za kriminološka i sociološka istraživanja, 2024)
In this paper, two different approaches to childhood in the history of "Western" feminism are presented. The first part of the paper is devoted to the key dispute in the relevant literature about whether feminists conceptualized childhood at all. Within this, the dominant viewpoint is firstly presented, according to which feminists did not write about childhood until the 1990s, in an effort to distance themselves from the patriarchal discourse that binds women to children. After that, the findings of the latest research from 2018/21 are presented, which show that feminists throughout history have written extensively on childhood, mostly theoretical/political discussions of the shared oppression that children and women suffer at the hands of adult men. The second part of the paper sheds light on the emergence of a different way of conceptualizing childhood in feminist texts in the 1990s, which is based on empirical research with children with a focus on the active re/construction of gender in their social interactions. In support of this, pioneering research from this period is presented, which paved the way for later, similar conceptualizations of childhood within this approach. The conclusion discusses the possibility of connecting these two approaches and their potential contribution to the sociology of childhood.